2014
DOI: 10.1242/jeb.108985
|View full text |Cite
|
Sign up to set email alerts
|

Allatostatin A-like immunoreactivity in the nervous system and gut of the larval midge, Chironomus riparius (Meigen): Modulation of hindgut motility, rectal K+ transport and implications for exposure to salinity

Abstract: Evidence for the presence of allatostatin (AST) A-like neuropeptides in the larval midge Chironomus riparius is reported. Immunohistochemical studies on the nervous system and gut revealed the presence of AST A-like immunoreactive (AST-IR) cells and processes. The nerve cord contained AST-IR processes that originated from cells in the brain and travelled the length of nerve cord to the terminal ganglion. Within each ganglion, these processes gave rise to varicosities, suggesting that they formed synapses with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
(85 reference statements)
1
7
0
Order By: Relevance
“…The PM contained two of the predicted neuropeptides. The presence of AstA peptides in the CNS and midgut has previously been reported in other dipterans including D. melanogaster [33,[35][36][37], the cabbage root fly Delia radicum larvae, the midge Chironomus riparius, and mosquitoes Aedes aegypti and Anopheles albimanus [36,[38][39][40][41].…”
Section: Distribution Of Detected Neuropeptidessupporting
confidence: 56%
“…The PM contained two of the predicted neuropeptides. The presence of AstA peptides in the CNS and midgut has previously been reported in other dipterans including D. melanogaster [33,[35][36][37], the cabbage root fly Delia radicum larvae, the midge Chironomus riparius, and mosquitoes Aedes aegypti and Anopheles albimanus [36,[38][39][40][41].…”
Section: Distribution Of Detected Neuropeptidessupporting
confidence: 56%
“…Chironomus riparius, Locusta migratoria and Lacanobia oleracea [700][701][702][703][704][705][706][707]. It is also possible that some of the peptides regulate activity in gut epithelial cells that produce digestive enzymes [28,208,708,709] or cells involved in nutrient or ion absorption [700,701,710].…”
Section: Gut Peptides and The Brain-gut Axismentioning
confidence: 99%
“…The neuroendocrinology of chironomids is an understudied area; however, a single study showed serotonin‐like immunoreactivity in the nervous system and gastrointestinal tract of a larval chironomid, Chironomus tentans (Johansson et al., ). This same study found immunoreactivity to several peptidergic factors and a second study mapped allatostatin‐like immunoreactivity in larval C. riparius (Robertson et al., ). Nothing is known about the potential regulation of chironomid Malpighian tubule activity by these or any other neuroendocrine factors.…”
Section: Introductionmentioning
confidence: 79%
“…Larval C. riparius physiologically respond to salinity by decreasing the activities of the ionomotive enzymes V‐type H + ‐ATPase and Na + /K + ‐ATPase in the rectal portion of the hindgut that reduces ion reabsorption from the rectal fluid (Jonusaite et al., ). This effect is mimicked by exogenous application of allatostatin, a peptidergic neuroendocrine factor, to the rectum, which is innervated by nerves containing an allatostatin‐like factor (Robertson et al., ). The results would suggest that more ions are left in the rectal fluid for excretion that would help deal with the increased ion load in the salinated conditions.…”
Section: Introductionmentioning
confidence: 99%